QUALITATIVE DESCRIPTION OF VERBAL AGREEMENT: PRONOMINAL ALTERNANCE BETWEEN NÓS AND A GENTE (Muitas Vozes, 2021)
Revisiting the grammatical literature (CUNHA; CINTRA, 2001; ROCHA LIMA, 2011; BECHARA, 2009; PERINI, 2005), opposed to other studies, e.g. Souza (2017), Tarallo (1985) and Monteiro (2008), this article aims to present a description of alternation between verb agreement patterns between personal pronouns nós (‘we’) and a gente (‘we’). For this purpose, we selected, by random sampling, an inquiry from the Iboruna database (GONÇALVES, 2007). We identified a preference for the use of a gente in relation to nós and to the elliptical subject; however, in the occurrences of the use of the personal pronoun nós, there is a preference by the informant for the verbal time in colloquial form, because it is presented as present perfect.